(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Child language acquisition is a fascinating area of study that examines how children learn their native languages. While there are universal stages every child goes through, the specifics can vary significantly across different languages. This article explores the similarities and differences in child language acquisition across various linguistic backgrounds.